2008
DOI: 10.1074/jbc.m707540200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-stimulated Basal Adenylyl Cyclase Activity Localization in Membrane Lipid Microdomains of Cardiac Sinoatrial Nodal Pacemaker Cells

Abstract: releases, which, in turn, activate ACs. This feed forward "fail safe" system, kept in check by a high basal phosphodiesterase activity, is central to the generation of normal rhythmic, spontaneous action potentials by pacemaker cells.Numerous studies over the past decade have indicated that intracellular Ca 2ϩ release is a key feature of normal cardiac pacemaker cell automaticity (1). More recently it has been demonstrated that the basal level of global cAMP in rabbit sinoatrial nodal cells (SANC) 3 exceeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 43 publications
6
125
0
Order By: Relevance
“…5A). We speculate that this increased rate may be a consequence of activation of the adenylate/cAMP pathway by Ca (35).…”
Section: Discussionmentioning
confidence: 99%
“…5A). We speculate that this increased rate may be a consequence of activation of the adenylate/cAMP pathway by Ca (35).…”
Section: Discussionmentioning
confidence: 99%
“…1), i.e., surface membrane electrogenic proteins, functioning as a voltage oscillator ("membrane clock"), and sarcoplasmic reticulum (SR) ( (2,19). This high-throughput Ca 2ϩ -calmodulin-activated AC/PKA-CaMKII-Ca 2ϩ release signaling cascade in pacemaker cells is regulated in a feed-forward manner (27,43) and requires physiological "brakes" to maintain the basal spontaneous action potential (AP) firing rate well below its maximum (Fig. 1).…”
mentioning
confidence: 99%
“…In brief, cDNA was synthesized in a 22 μL reaction per sample with 2 μg total RNA, 0.5 μg/μL oligo (dT) 12-18 , 0.5 μL 20 U RNAsin (Promega, Madison, WI, USA), 4 μL of 5× RT buffer, 5 μL of 2.5 mM dNTPs, and 20 U Moloney murine leukemia virus RT enzyme (Invitrogen). Semi-quantitative polymerase chain reaction (PCR) was performed with the TPersonal Thermocycler System from Biometra (Göttingen, Germany), all primer sequences were adopted from (Younes et al 2008) and shown in Table 1. Each reaction contained 1 μL cDNA, MgCl 2 of 3 mM final concentration in case of AC1, otherwise 2.5 mM, 2.5 mM dNTP, 5 μL 10× RT buffer, 1 pmol of each primer, and 0.25 μL 5 U A-Taq polymerase (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%